A combined experimental and in silico approach to determine the compatibility of poly(ester amide)s and indomethacin in polymer nanoparticles. (5th August 2021) - Muljajew, Irina; Chi, Mingzhe; Vollrath, Antje; Weber, Christine; Beringer-Siemers, Baerbel; Stumpf, Steffi; Hoeppener, Stephanie; Sierka, Marek; Schubert, Ulrich S.
Graphical abstract: Highlights: Cross comparison between formulation, bulk properties and simulation. Minor differences in polymer structure determine nanoparticle formulation ability. Consistent Flory-Huggins parameter by DSC and molecular dynamics simulations. Substituent structure of the poly(ester amide)s determines compatibility with drug. in silico determined H-bonding between polymer-drug rationalizes compatibilities. Abstract: The development of optimized carrier materials for the encapsulation of new high-potency drugs is frequently hampered by the need for trial-and-error experiments. Combining experimental and in silico approaches with a feedback loop is a promising way to overcome this drawback. Here, such a combined study is conducted to investigate the compatibility and the underlying interactions of the anti-inflammatory drug indomethacin (IMC) and six poly(ester amide)s (PEA). Optimization of nanoparticle formulation conditions via a high-throughput nanoprecipitation screening yielded particles in the desired size range of 100 to 400 nm. Formulation of IMC loaded PEA nanoparticles with reduced surfactant impact indicated strong influence of the polymer structure and density on the polymer performance. Differential scanning calorimetry of PEA and IMC blends enabled access to saturation conditions (7 to 18% at 111 °C) and pointed towards thermodynamic compatibility (Flory-Huggins (FH) interaction parameters −0.20 to −0.52). FH parameters from atomistic molecular dynamics simulations were found to be in agreement with the experimental values, additionally rationalizing the PEA-drug compatibilities through hydrogen bonding interactions. Cross comparison of all elements of the study showed that both compatibility and nanoparticle formation ability contribute to the encapsulation efficiency.